Stability constants and stoichiometries of chromium and zirconium carboxylates complexes calculated by four comparative methods - Omar, Abdalazeem; Ali, Elmugdad (International Journal of Advanced Chemistry, 2015)
Four comparative methods for determination of stoichiometries and stability constants of chromium and zirconium complexes with citric and propanoic acids were studies, in purpose to select the most accurate and sensitive method, and to compare the formation of complexes of these two transition metals. (Cr 1st transition series group 6B, Zr 2nd transition series group 4B)Metal-ligand stability constants and stoichiometries of the above systems were determined by Calvin & Bjerrum pH-metric titration technique as adopted by Irving & Rossotti.Four methods employed were point-wise calculation method, half integral method, linear plot method and least squares method. The result seems in a good agreement with each other and any method can represents the other.